2005
DOI: 10.1007/s00011-004-1319-4
|View full text |Cite
|
Sign up to set email alerts
|

Increase in macrophage elastase (MMP-12) in lungs from patients with chronic obstructive pulmonary disease

Abstract: This study demonstrated that COPD patients produce greater quantities of MMP-12 than controls, which may be a critical step in the pathogenesis of COPD and emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(130 citation statements)
references
References 19 publications
5
124
1
Order By: Relevance
“…In this study, our data demonstrate that over-activation of TGFβ1 together with MMP2 and MMP12 expression at the mRNA level in WT mice, which is partly in accordance with the previous reports that increased MMPs at the protein level were seen in patients with emphysema [27,28] , have tissue destructive and fibrotic effects depending on the location (either in parenchyma or in airways) [31] . It should be pointed out that the current study was based on a short-term exposure model.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, our data demonstrate that over-activation of TGFβ1 together with MMP2 and MMP12 expression at the mRNA level in WT mice, which is partly in accordance with the previous reports that increased MMPs at the protein level were seen in patients with emphysema [27,28] , have tissue destructive and fibrotic effects depending on the location (either in parenchyma or in airways) [31] . It should be pointed out that the current study was based on a short-term exposure model.…”
Section: Discussionsupporting
confidence: 92%
“…Elias and colleagues have provided evidence that these enzymes may be regulated by proximal immune events through a Th1 cell-or IFNγ-dependent manner [26] . T cells, particularly CD8+ T cells, accumulate in the lungs of patients with COPD and generate signals such as CXCL10/ IP-10 that promote MMP12 production by macro phages [27,28] . Moreover, CXCR3 expressed by human T cells and macrophages is required for MMP12 secretion in response to IP-10/Mig stimulation [24] .…”
Section: Discussionmentioning
confidence: 99%
“…These cells preferentially traffic to sites of inflammation. The preferential recruitment of these proinflammatory cells provides an abundant source of a number of proteases including cathepsins K, L, and S, as well as MMPs-1, -2, -9, and -12, and the production of these proteases appears to be elevated in lung macrophages in patients with COPD both in vivo and ex vivo (57)(58)(59)(60)(61).…”
Section: The Nature Of Inflammatory and Cellular Infiltration In Copdmentioning
confidence: 99%
“…Enhanced MMP-12 activity was also detected in BAL fluids from patients with COPD in comparison with control subjects. The study in question demonstrated that COPD patients produce greater quantities of MMP-12 than controls, which may be a critical step in the pathogenesis of COPD and emphysema (23). Studies using MMP-12 knock-out (KO) mice have demonstrated that macrophage recruitment in lungs and emphysema induced by long-term exposure to cigarette smoke were linked to MMP-12 (24).…”
Section: Role Of Mmp In the Development Of Airway Inflammation In Chrmentioning
confidence: 99%